Functionalized Membrane Domains: An Ancestral Feature of Archaea? - Tourte, Maxime; Schaeffer, Philippe; Grossi, Vincent; Oger, Phil M. (Frontiers in Microbiology, 2020)
Bacteria and Eukarya organize their plasma membrane spatially into domains of distinct functions. Due to the uniqueness of their lipids, membrane functionalization in Archaea remains a debated area. A novel membrane ultrastructure predicts that monolayer and bilayer domains would be laterally segregated in the hyperthermophilic archaeon Thermococcus barophilus. With very different physico-chemical parameters of the mono- and bilayer, each domain type would thus allow the docking of different membrane proteins and express different biological functions in the membrane. To estimate the ubiquity of this putative membrane ultrastructure in and out of the order Thermococcales, we re-analyzed the core lipid composition of all the Thermococcales type species and collected all the literature data available for isolated archaea. We show that all species of Thermococcales synthesize a mixture of diether bilayer forming and tetraether monolayer forming lipids, in various ratio from 10 % to 80 % diether in Pyrococcus horikoshii and Thermococcus gorgonarius respectively. Since the domain formation prediction rests only on the coexistence of di- and tetraether lipids, we show that all Thermococcales have the ability for domain formation, i.e. differential functionalization of their membrane. Extrapolating this view to the whole Archaea domain, we show that almost all archaea also have the ability to synthesize di- and tetraether lipids, which supports the view that functionalized membrane domains may be shared between all Archaea. Hence domain formation and membrane compartmentalization may have predated the separation of the three domains of life and be essential for the cell cycle.